2020
DOI: 10.1002/brb3.1576
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intrathecal injection of muscimol and endomorphin‐1 alleviates neuropathic pain in rat model of spinal cord injury

Abstract: Introduction Due to side effects of medications used for chronic pain, combination therapy seems to be an appropriate solution for alleviation of chronic pain and reducing the side effects. The role of inhibitory GABA system is well proven in reducing neuropathic pain. Also, special attention has been focused on endogenous morphine (endomorphins) in reducing chronic pain originates from damage to the nervous system. The purpose of this study is to investigate the analgesic effect of simultaneous administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…41 Furthermore, alterations in inhibitory neurotransmitters' content and receptor expression occurred at Day 1 post-SCI compared to pre-SCI level, and to control-and/or shamoperated animals. 8,21,25 These studies suggest that a reduction in inhibitory control was acquired after SCI and support the temporal pattern of events in this study. Brain imaging studies reported maladaptive metabolism, structural changes, and connectivity in pain modulation structures among people with chronic CNP, compared to controls, which correlated with pain severity.…”
Section: Pain Inhibition After Spinal Cord Injurysupporting
confidence: 86%
“…41 Furthermore, alterations in inhibitory neurotransmitters' content and receptor expression occurred at Day 1 post-SCI compared to pre-SCI level, and to control-and/or shamoperated animals. 8,21,25 These studies suggest that a reduction in inhibitory control was acquired after SCI and support the temporal pattern of events in this study. Brain imaging studies reported maladaptive metabolism, structural changes, and connectivity in pain modulation structures among people with chronic CNP, compared to controls, which correlated with pain severity.…”
Section: Pain Inhibition After Spinal Cord Injurysupporting
confidence: 86%
“…The neuropathic pain was assessed by Von Frey monofilaments (Hosseini et al., 2020). Briefly, the animals were located in a cage with a wire mesh grid, provided access to the rats’ paws from the cage's floor.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Corbett 1991, demonstrate that muscimol improved social behaviour and had anxiolytic-like effects post systemic administration to test rats, similar to diazepam [ 112 ]. Additionally, muscimol when used as a combination therapy with endomorphin-1 reduced the symptoms of neuropathic pain due to spinal cord injury when administered for 7 consecutive days [ 113 ]. Bufotenine (5-HO-DMT) is an alkaloid and a substituted tryptamine similar to serotonin and psilocin, also present in the Amanita mushroom.…”
Section: Fungal Biologics: Unlocking the Potential Of Eastern Practic...mentioning
confidence: 99%